Revisiting dominant notions: a review of costs, performance and institutions of small reservoirs in Sub-Saharan Africa - Venot, Jean-Philippe; Fraiture, Charlotte de; Nti Acheampong, Ernest (International Water Management Institute, 2012)
This report investigates the dynamics of one of the most common agricultural water management practices of Sub-Saharan Africa, i.e., small reservoirs. Small reservoirs dam permanent or temporary river flows and support multiple livelihood activities (livestock watering, crop cultivation, fisheries, small handicrafts, etc.) while providing water-related ecosystem services (soil and water conservation, flood and drought mitigation, etc.). Gathering evidence from four sub-Saharan countries, Burkina Faso, Ghana, Ethiopia and Zambia, this report calls for revisiting our understanding and assessment of the costs, performance and institutions for the management of small reservoirs. A more holistic analytical approach is the first step towards an integrative governance framework. This, in turn, holds the promise of sustainable management of small reservoirs.